1991
DOI: 10.1111/j.1365-2796.1991.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic autoantibodies and pancreatic function in Sjögren's syndrome

Abstract: Pancreatic autoantibodies were determined in 49 patients with Sjögren's syndrome and related to functional parameters. Pancreatic duct autoantibodies (PDA) were detected in the sera of three patients, and all showed abnormal exocrine pancreatic function. Islet cell antibodies (ICA) were not detected in the sera of the 49 patients, including two individuals with diabetes mellitus. In conclusion, PDA occur in patients with Sjögren's syndrome, and may be associated with exocrine pancreatic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, antibodies reactive with pancreatic ductal cells have been zyme levels, exocrine pancreatic function studied by the BT-PABA excretion test, and pancreatic ductal morpholreported in patients with SjS. 11,12 It has been proposed that a disease complex exists that ogy classified by ERP among the two groups. Antinuclear antibody was observed with a significantly higher prevaincludes patients with SjS, CP, PBC, primary sclerosing cholangitis, and renal tubular acidosis, and this disease lence rate in patients with CP with anti-CAII antibody, but rheumatic factor was not observed with a higher rate.…”
Section: Specificity Of Serum Antibodies Against Cai or Caii In Patiementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, antibodies reactive with pancreatic ductal cells have been zyme levels, exocrine pancreatic function studied by the BT-PABA excretion test, and pancreatic ductal morpholreported in patients with SjS. 11,12 It has been proposed that a disease complex exists that ogy classified by ERP among the two groups. Antinuclear antibody was observed with a significantly higher prevaincludes patients with SjS, CP, PBC, primary sclerosing cholangitis, and renal tubular acidosis, and this disease lence rate in patients with CP with anti-CAII antibody, but rheumatic factor was not observed with a higher rate.…”
Section: Specificity Of Serum Antibodies Against Cai or Caii In Patiementioning
confidence: 99%
“…Results: Serum antibodies against carbonic serum antibodies that react with duct cells in salivary anhydrase I and II were detected in 7 and 11 of 33 glands and pancreas [11][12][13][14][15] ; however, the molecular nature patients with idiopathic chronic pancreatitis, respectively, and in 8 and 13 of 21 patients with Sjögren's of this antigen has not been determined.…”
mentioning
confidence: 99%
“…On the other hand, from the clinical perspective, a disease complex including CP, SjS, PBC, and/or renal tubular acidosis has been proposed as a new disease entity with the name of "dry gland syndrome" (13) or ''autoimmune exocrinopathy" (14). In particular, the pancreatic insufficiency has been well documented (36)(37)(38)(39)(40)(41)(42). The present study showed that serum of patients with idiopathic CP and SjS reacted with a common antigen in the duct cells of exocrine organs, supporting the above hypothesis.…”
Section: Discussionmentioning
confidence: 99%